PENGUJIAN BLACK BOX TESTING PADA APLIKASI ACTION & STRATEGY BERBASIS ANDROID DENGAN TEKNOLOGI PHONEGAP - Iqbal Fahrozi; Anzal Fadly Hadi Pratama; Yusri Nuraeni; Rendi Pratama Juniar (CV. Multi Kreasi Media, 2023)
Android technology today has developed into the daily needs of the public and workers. Therefore, it is necessary to build an Android-based action & strategy application as a knowledge sharing media for Brimob members to improve the quality of each personnel. However, to get optimal results, it is important to perform a thorough test on the application system interface by using black box testing with the aim of knowing whether the functions in the application have run according to their objectives and of evaluating the application suitability for the user's needs. The test is carried out in two stages. The first test is performedon the functions of the android application simultaneously conducted by a number of users. The secondtest is carried out on the administration web functionsconducted by a user. The results of the two tests show no system error. The method used to conduct the tests for this research is a quantitative method.